The relationship between dietary habits of late adolescent individuals and the heavy metal accumulation in hair - Gonener, Ahmet; Ersoy Karacuha, Melek; Cabar, Huriye Demet; Yilmaz, Muhitdin; Gonener, Utku (Progress in Nutrition, 2020)
Study Objectives: This study aimed to determine the effects of smoking status and dietary habits on heavy metal accumulation in late adolescent students studying at Sinop University. Methods: This experimental research was conducted between 09 October and 15 November 2019. The population of the study was composed of 18-21 age (late adolescent period) students studying at Sinop University, School of Health. In the determination of the research sample, the selection of students who accepted to participate in the research as the case selection criteria, who did not have any mental or chronic disease/syndrome, and who did not use drugs continuously was taken into consideration. For the collection of research data, an information form about the weekly consumption of foods and smoking status was prepared by the researchers considering the geographical and physical locations where the students are located. After collecting the forms filled by students, 0.5 g hair samples were taken from volunteered 41 students to analyze the concentration of heavy metal in the hair and analyzed in the ICP-MS device. The data were evaluated using the Mann-Whitney U test in the SPSS (version 22.0) statistical program. Results: As a result of this research, it has been revealed that there was a statistically significant relationship between some food groups (lettuce, chips, instant soup, salami, and trout) that students express at least once a week and the heavy metal concentration detected in their hair. Conclusion: It was revealed that there is a relationship between individuals’ dietary habits and heavy metals in late adolescence.